Use of argyrophilic nucleolar–organizer region-associated protein synthesis in skeletal muscle cells for prediction of chronic carbon monoxide exposure. (1st October 2020) - Gunes, Harun; Saritas, Ayhan; Eroz, Recep; Colakoglu, Serdar
Abstract: This study aims to evaluate possible effects of chronic carbon monoxide (CO) exposure on argyrophilic nucleolar–organizer region (AgNOR)-associated protein synthesis in striated muscle cells. Eighteen rats were randomly divided into three groups. Rats in group II and group III were given CO gas (1000 and 3000 ppm, respectively) for 30 min a day for 7 d. Mean AgNOR number per nucleus and ratio of total AgNOR area to nuclear area (TAA/NA) were determined. Both TAA/NA ratio and mean AgNOR number provided information about the existence or absence of exposure. TAA/NA ratio was also an indicator of the level of exposure.